THU0156 Achievement of Low Disease Activity in Patients Initiating Infliximab with and without Dose Escalation. (15th July 2016) - Cohen, S.; Reed, G.; Magner, R.; Kafka, S.; Ellis, L.; DeHoratius, R.J.; Greenberg, J.D.
Abstract : Background: Dose escalation is a common strategy for patients (pts) having an inadequate response to a medication. Objectives: To examine low disease activity (LDA) among pts receiving infliximab (IFX) who did and did not escalate therapy above 3mg/kg in CORRONA, a US national registry of rheumatoid arthritis (RA) pts. Methods: We identified all RA pts who initiated IFX on or after 6/2009 at a dose ≤3mg/kg and with moderate or high disease activity (CDAI>10). Eligible pts required at least 6 mos of follow-up after initiation or after dose escalation. Dose escalation was defined as an increase of >1mg/kg or reduction in infusion intervals by ≥1 wk. We divided pts into 3 groups: pts achieving LDA (CDAI ≤10) without dose escalation; pts not achieving LDA and not dose escalating; pts dose escalating. The last group was further divided into pts achieving LDA after dose escalation and pts not achieving LDA after dose escalation. We compared the populations at time of initiation by demographics, BMI in categories of normal (BMI<25), overweight (25≥BMI<30), obese (BMI ≥30), disease characteristics and activity, comorbidities (including diabetes), and medications (prior and current conventional disease modifying anti-rheumatic agents or biologics). For dose escalators, we determined the last dose at time of LDA or in those not achieving LDA, the last dose. The dose is normalized to mg/kg/8wk for comparative purposes. Results: There were 286 pts who met inclusion criteria. 124 (43.4%) reached LDA without escalation; 50 (17.5%) either switched without escalation or had not reached LDA by at least 9 mos; 112 (39.2%) escalated. Of the escalators, 64 (57.1%) reached LDA and 48 (42.9%) switched or did not reach LDA by at least 9 mos. Pts who reached LDA without escalation were more likely to be biologic naïve (67.7%) than those who escalated but did not reach LDA (45.8%, p=0.008). Pts reaching LDA without escalation had lower disease activity measures at initiation (tender joints, physician global assessment, pt global assessment, pt pain) than pts not reaching LDA with or without escalation (p<0.05 for all measures). However, swollen joint counts were not significantly different. Pts escalating had higher rates of obesity (57%) and diabetes (13.4%) than pts reaching LDA without escalating (obesity: 41% [p=0.02] and diabetes: 5.7% [p=0.046]). Pts not reaching LDA after escalation had the highest rate of obesity (62.5%). Pts reached LDA at a median dose of 6.0mg/kg/8wks, Interquartile Range (IQR): [5, 8]; pts not reaching LDA had a final median dose of 6.7mg/kg/8wks, IQR: [5, 8.5]. There was no significant difference in last dose by BMI group. Conclusions: Pts more likely to reach LDA without dose escalation are biologic naïve and have lower disease activity measures at initiation. Both high BMI (obese) and diabetes are associated with requiring dose escalation to achieve LDA. In this analysis, ≤25% of patients received dose escalation beyond 8mg/kg/8wks, which may have clinical relevance. Acknowledgement: Study sponsored by Corrona, LLC. Corrona RA registry has been supported thru contracted subscriptions in last 2 yrs by AbbVie, Amgen, BMS, Crescendo, Genentech, Horizon Pharma USA, Janssen, Eli Lilly, Novartis, Pfizer, & UCB. Disclosure of Interest: S. Cohen Grant/research support from: Amgen, Biogen-IDEC, BMS, Centocor, Genentech, Johnson & Johnson, Pfizer, Merck, and Roche, G. Reed Shareholder of: Corrona, LLC, Employee of: Corrona, LLC, R. Magner Employee of: Corrona, LLC, S. Kafka Employee of: Janssen Scientific Affairs, LLC, L. Ellis Employee of: Janssen Scientific Affairs, LLC, R. DeHoratius Employee of: Janssen Scientific Affairs, LLC, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: Janssen Scientific Affairs, LLC, AstraZeneca, Celgene, Genentech, Novartis, Pfizer, Employee of: Corrona, LLC